2004
DOI: 10.1023/b:biom.0000029432.69418.6a
|View full text |Cite
|
Sign up to set email alerts
|

The structure of salmochelins: C-glucosylated enterobactins of Salmonella enterica§

Abstract: Salmochelins represent novel carbohydrate containing catecholate siderophores, which are excreted by Salmonella enterica and uropathogenic Escherichia coli strains under low-iron stress. While previous analytical data showed salmochelins to contain 2,3-dihydroxybenzoyl-L-serine and glucose, the molecular structure remained elusive. Structure elucidation with electrospray ionization-Fourier transform ion cyclotron resonance-mass spectrometry (ESI-FTICR-MS), GC-MS and 2D-NMR now revealed that salmochelins are en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
199
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(204 citation statements)
references
References 27 publications
3
199
0
2
Order By: Relevance
“…Rather than Ent, iroAharboring bacteria secrete a mixture of salmochelins S4 and S2 ( Fig. 1 A), which are macrocyclic and linearized versions of diglucosylated Ent, respectively (16,17). We have shown that glucosylation and linearization of Ent decrease its propensity to partition into lipid bilayers, which might be advantageous for iron scavenging in a membrane-rich microenvironment (18).…”
mentioning
confidence: 91%
“…Rather than Ent, iroAharboring bacteria secrete a mixture of salmochelins S4 and S2 ( Fig. 1 A), which are macrocyclic and linearized versions of diglucosylated Ent, respectively (16,17). We have shown that glucosylation and linearization of Ent decrease its propensity to partition into lipid bilayers, which might be advantageous for iron scavenging in a membrane-rich microenvironment (18).…”
mentioning
confidence: 91%
“…Molecular characterization demonstrated that salmochelins are glucosylated versions of enterobactin (Bister et al, 2004). There are several potential advantages of enterobactin glucosylation.…”
Section: (B) Salmochelinsmentioning
confidence: 99%
“…This ability is necessary for their survival and proliferation in the iron-poor environment of tissues and cells, and, as a result, siderophores are often considered potential virulence factors. Salmochelins in particular seem to be superior siderophores, compared with enterobactin, in the presence of serum albumin; therefore, it has been suggested that salmochelins may play a significant role in some infections (10).…”
Section: Irob Modifies An Iron Chelator That Is a Potentialmentioning
confidence: 99%